Reaction-driven magmatic crystallisation at the Maoniuping carbonatite - Yan Liu; Michael Anenburg (Nature Communications)
Abstract Igneous rocks form by solidification of magmas through cooling or volatile degassing following decompression. Expelled H2O is thought to trigger alteration around intrusions, leading to formation of metasomatic halos. This mechanism is often invoked to explain many magmatic–hydrothermal rock associations, some of them economically mineralised. Maoniuping in China is one of the four largest operating rare earth element (REE) mines globally, whose origin has been attributed to such hydrothermal exsolution. However, no direct evidence links hydrothermal fluids to the formation of Maoniuping and its associated REE mineralisation. Here we show that the REE deposit at Maoniuping formed magmatically from a carbonatitic brine-melt. Textural and chemical evidence reveals extensive interaction with its quartz syenite host, producing albitised fenites. Coupled metasomatism with these fenites led to silica contamination of the carbonatite melt, triggering crystallisation of refractory alkali–ferromagnesian silicates—an antiskarn. This solidified the melt due to removal of the fluxing elements Na and K. Thus, carbonatite melts can crystallise by element assimilation from their environments, precipitating alkali liquid fluxes into solid minerals. Temperature decrease and volatile degassing merely play a secondary role in this igneous rock-forming process. Solidification driven by coupled antiskarnisation and fenitisation affects both the mineral assemblage and ore fabric, and likely operated in most carbonatite-hosted REE deposits elsewhere.